The neurogenic bladder: developing a consensus bladder and bowel management pathway for people with MS. (24th November 2022) - Thomas, Sue; Bradley, Joan; Cole, Georgina; Girvan, Marie; Metcalfe, Gale; Naik, Paru; Owen, Audrey; Solomons, Margaret; Stross, Ruth; Yates, Ann; Webb, Mark; White, Sarah; et al.
Abstract : This article outlines how the bladder can be affected in neurological conditions such as multiple sclerosis (MS) and the impact this has on patient quality of life and NHS resources. A group of MS and bladder and bowel nurse specialists has developed consensus bladder pathways in the hope that all nurses in contact with patients who are likely to have neurogenic bladder symptoms become 'bladder aware'.